Penentuan Kebutuhan Pokok Protein Pada Napu (Tragulus napu) - Latief, Abdul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The study aimed to determine the protein requirements for basic life and growth on Napu. Four Napus with an average 3.2 kg body weight were used in this study. 4 X 4 Latin square design was used in this research. Feed treatment were contained four levels of protein, namely 10%, 15%, 20% and 25%. ResearchÂ results showed that protein levels did not significantly affect dry matter intake, nitrogenÂ in faeces and nitrogen in urine. Consumption of nitrogen at levels 25% was higher (P <0.05) than 10%, 15% and 20% 0f protein level. Consumption of nitrogen on the protein level 10% and 15% were not significantlyÂ different.Â NitrogenÂ balanceÂ increasedÂ (PÂ <0.05)Â withÂ increasedÂ levelsÂ ofÂ proteinÂ inÂ feed. Retention of total nitrogen at the highest protein level was 0.92 g / kg BW and in the lowest level of 0.25 g/kg BW. The highest body weight gain was obtained at the protein level of 25% followed by the level of 20%, 15% and 10%. BW gain was not significantly different from the retention of nitrogen (R2= 0896). NitrogenÂ requirementÂ wasÂ estimatedÂ atÂ theÂ timeÂ ofÂ retentionÂ ofÂ nitrogenÂ equalÂ toÂ zeroÂ ieÂ 0.20Â g/kg BW/day, equivalent to 8.1% protein in feed. Nitrogen requirement for growth is 0.67 g N/kg BW/day, equivalent to 20.4% protein in feed